A comparative evaluation of waste wood and herbaceous biomass fireside corrosion behaviours - Sanusi, Toyin; Sumner, Joy; Simms, Nigel J. (Elsevier, 2022)
Biomass/biomass waste (BBW) is a renewable energy source fired in combustion power plants. However, challenges associated include accelerated ‘fireside’ corrosion of heat exchangers. Fireside corrosion is fuel dependent, e.g. virgin wood fuels have lower fireside corrosion risks; as such their demand and cost is high. Waste wood fuels (WWF) and herbaceous grass biomass (HGB), generate different combustion environments, influencing heat exchanger fireside corrosion damage. This paper compares the fireside corrosion of WWF and HGB fuels to improve understanding of their attack mechanisms on T91 and 374HFG. The species generated in combustion have been investigated by thermodynamic modelling. Corrosion damage has been evaluated by high temperature corrosion furnace tests at 600 °C, employing the well-established deposit recoat method based on these evolved species. Vapour condensation fluxes have been compared for both fuel categories; corrosion rates increase with this condensation flux. Deposition fluxes from HGB fuels are higher than for WWF. For example, the average KCl deposition fluxes calculated are 1566 µg/cm2h and 295 µg/cm2h per kg fuel feed respectively, explaining the comparatively greater fireside corrosion rates experienced in power plants combusting HGB fuels. The deposit chemistries generated are also different: K-containing compounds only (for HGB fuels) versus K-, Na- and Ca-containing compounds (for WWF). Evaluation of corroded samples exposed to the different deposit chemistries show increased corrosion attack to both steels under simulated WWF firing conditions than for the HGB at matched deposit flux (100 µg/cm2h).
Keywords: Fireside corrosion; Biomass and waste combustion; Condensation rate; Thermodynamics; Cation mechanisms